NATURAL LIGHTING AND NATURAL VENTILATION ON THERMAL COMFORT AND ENERGY EFFICIENCY IN COLONIAL HERITAGE BUILDINGS. - Andiyan Andiyan; Ikaputra Ikaputra (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: Natural lighting and natural ventilation are very important in the architecture of cultural heritage buildings, especially concerning thermal comfort and energy efficiency. This study aims to explore the impact of these two elements on the design of cultural heritage buildings in tropical climates. The method used is a systematic literature review, highlighting the latest relevant scientific articles. The results of the study show that the optimal use of natural lighting and ventilation can improve occupant comfort. A reduction in indoor temperature of up to 5°C can also decrease the energy requirements for cooling and lighting. In addition, passive design strategies that consider building orientation and the use of local materials have proven effective in managing heat and humidity loads. These conclusions are expected to serve as a reference for practitioners and managers of heritage buildings. By applying sustainable design principles, they can maintain the historical integrity of buildings while achieving better energy performance. Keywords: Natural lighting, Natural ventilation, Thermal comfort, Energy efficiency, Heritage buildings, Passive design. Abstract: Pencahayaan alami dan penghawaan alami sangat penting dalam arsitektur bangunan cagar budaya, terutama terkait dengan kenyamanan termal dan efisiensi energi. Penelitian ini bertujuan untuk mengeksplorasi dampak kedua elemen tersebut dalam desain bangunan cagar budaya di iklim tropis. Metode yang digunakan adalah tinjauan literatur sistematis, menyoroti artikel-artikel ilmiah terbaru yang relevan.Hasil penelitian menunjukkan bahwa pemanfaatan optimal pencahayaan alami dan ventilasi dapat meningkatkan kenyamanan penghuni. Penurunan suhu dalam ruangan mencapai 5°C juga dapat mengurangi kebutuhan energi untuk pendinginan dan pencahayaan. Selain itu, strategi desain pasif yang memperhatikan orientasi bangunan dan penggunaan material lokal terbukti efektif dalam mengelola beban panas dan kelembapan.Kesimpulan ini diharapkan menjadi acuan bagi praktisi dan pengelola bangunan cagar budaya. Dengan menerapkan prinsip-prinsip desain berkelanjutan, mereka dapat mempertahankan integritas historis bangunan sambil mencapai kinerja energi yang lebih baik. Kata Kunci: Pencahayaan alami,Penghawaan alami,Kenyamanan termal,Efisiensi energi,Bangunan cagar budaya,Desain pasif.